2021
DOI: 10.1186/s12891-021-04439-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct reduction of high-grade lumbosacral spondylolisthesis with anterior cantilever technique - surgical technique note and preliminary results

Abstract: Backgrounds Surgical reduction for high-grade spondylolisthesis is beneficial for restoring sagittal balance and improving the biomechanical environment for arthrodesis. Compared to posterior total laminectomy and long instrumentation, anterior lumbar inter-body fusion (ALIF) is less invasive and has the biomechanical advantage of restoring the original disk height and increasing lumbar lordosis, thus improving sagittal balance. However, the application of ALIF is still limited in treating low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…This is similar to blood loss values reported in the literature. Tu et al (2021), for example, found a mean blood loss of 300ml, and Teng et al (2017) report a mean blood loss of 200-300ml, which, however, can increase drastically in the case of vascular injury (4,22). Blood loss associated with venous vessel injury ranged from 250ml to 10,000ml in our sample.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…This is similar to blood loss values reported in the literature. Tu et al (2021), for example, found a mean blood loss of 300ml, and Teng et al (2017) report a mean blood loss of 200-300ml, which, however, can increase drastically in the case of vascular injury (4,22). Blood loss associated with venous vessel injury ranged from 250ml to 10,000ml in our sample.…”
Section: Discussionmentioning
confidence: 43%
“…Most studies investigating the reduction of spondylolisthesis after ALIF have relatively low sample size numbers, with case numbers between 5 and 65 participants (3-5, 11, 13, 14, 17) and most studies having fewer than 30 participants (4,5,11,14,17). With 96 cases, we present, to our knowledge, one of the most extensive single-center studies investigating this topic.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lamartina [1] presents satisfactory short-te outcomes with the reduction in the deformity using the PLIF technique wit interbody fusion. In the case of smaller slips, good results were achieved by tion of posterior reduction and anterior interbody fusion using the ALIF techn new technique presented in the literature describes a combination of appro posterior mono-segmental stabilization and anterior direct reduction in the sli anterior cantilever procedure [32]. The authors achieved a high fusion rate reduction in the slip, and improved the anatomy of the LS junction.…”
Section: Discussionmentioning
confidence: 99%
“…ALIF can be used in cases of isthmic spondylolisthesis as well as degenerative spondylolisthesis. While some authors routinely use ALIF alone for spondylolisthesis cases [ 2 , 3 ], others combine it with dorsal instrumentation for these patient groups [ 4 ]. Dorsal instrumentation also provides better long-term fusion rates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%